Robotic‐assisted minimally invasive surgery of the spine (RAMISS): a proof‐of‐concept study using carbon dioxide insufflation for multilevel posterior vertebral exposure via a sub‐paraspinal muscle working space. Issue 3 (19th October 2016) - Howard, Jason J.; Abinahed, Julien; Navkar, Nikhil; Peyrat, Jean‐Marc; Al‐Ansari, Abdulla; Sigalet, David L.; Zarroug, Abdalla E.
Abstract: Background: Open posterior spinal procedures involve extensive soft tissue disruption, increased hospital length of stay, and disfiguring scars. Our aim was to demonstrate the feasibility of using robotic‐assistance for minimally invasive exposure of the posterolateral spine with and without carbon dioxide (CO2 ) insufflation. Methods: Sheep specimens underwent minimally invasive subperiosteal dissection of the spine during three trials. The da Vinci S Surgical system was used for access with and without working space support via CO2 insufflation. Results: Without insufflation, a sub‐paraspinal muscle tunnel measuring 16 cm was developed between two 5 cm incisions. With insufflation, the one‐sided tunnel length was 12.5 cm but without the soft tissue trauma and obstructed visualization experienced without CO2 . Conclusions: The use of robot‐assistance for minimally invasive access to the posterior spine appears to be feasible. The use of CO2 insufflation greatly improved our ability to visualize and access the posterior vertebral elements.